2021
DOI: 10.1007/s12265-021-10110-2
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Respiratory Failure Can Impair Myocardial Oxygenation in Patients with Acute Cardiogenic Shock Supported by VA-ECMO

Abstract: Venous-arterial extracorporeal membrane oxygenation (VA-ECMO) treatment for acute cardiogenic shock in patients who also have acute lung injury predisposes development of a serious complication called “north-south syndrome” (NSS) which causes cerebral hypoxia. NSS is poorly characterized and hemodynamic studies have focused on cerebral perfusion ignoring the heart. We hypothesized in NSS the heart would be more likely to receive hypoxemic blood than the brain due to the proximity of the coronary arteries to th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 24 publications
0
14
0
Order By: Relevance
“…Given the native LV contractility, the deoxygenated blood is then ejected into the ascending aorta. As a result, a mixing cloud forms between the anterograde flowing deoxygenated blood and the fully oxygenated retrograde flow provided by the circuit ( 179 ) ( Figure 1 ). The location of the mixing cloud depends on the native cardiac function and the level of competing ECMO flow.…”
Section: Complications Of Va-ecmo Supportmentioning
confidence: 99%
“…Given the native LV contractility, the deoxygenated blood is then ejected into the ascending aorta. As a result, a mixing cloud forms between the anterograde flowing deoxygenated blood and the fully oxygenated retrograde flow provided by the circuit ( 179 ) ( Figure 1 ). The location of the mixing cloud depends on the native cardiac function and the level of competing ECMO flow.…”
Section: Complications Of Va-ecmo Supportmentioning
confidence: 99%
“…However, their neurological symptoms were relieved after improving upper body oxygenation. Previous studies have also suggested that in patients receiving femo-femoral VA ECMO with respiratory circulatory failure, myocardial hypoxia occurred as residual cardiac function increased (30). Coronary oxygen saturation was measured using proximal aortic oxygen saturation, and coronary oxygen insufficiency has been demonstrated in patients (9).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the reliability of SrO 2 at anticipating risk of ischemic cerebral events remains controversial. It is important to note that most studies have focused on early identification of cerebral ischemia, however in differential hypoxemia, myocardial ischemia will occur sooner due to the nature of arterial anatomy (coronaries are proximal to carotid arteries) [14]. Monitoring trends in ECG, cardiac biomarkers, and echocardiography may assist in timely recognition of myocardial ischemia in mixed cardiorespiratory disease.…”
Section: Key Pointsmentioning
confidence: 99%